Conceptual design study based on defined parameters for next-generation Martian rotorcrafts - Youhanna, Vishal; Felicetti, Leonard; Ignatyev, Dmitry (Institute of Electrical and Electronics Engineers (IEEE), 2024)
The remarkable achievement of NASA’s Ingenuity Helicopter has opened exciting possibilities for the future exploration of Mars, suggesting that aerobots will play a crucial role alongside rovers and landers. However, Ingenuity’s capabilities are limited by its small and relatively basic design. This limitation is primarily evident in its restricted long-range endurance and limited capacity for scientific payloads. To address these shortcomings and advance the field of Martian drone technology, this paper introduces a practical approach to optimising the Martian rotorcraft concepts within the set parameters. The primary objective of these concepts is to enhance performance, endurance, and payload capacity to meet more demanding requirements for future Martian aerobot missions. The paper addresses an essential phase in the design process—an initial sizing of rotary electric vertical takeoff and landing (eVTOL) configurations. This phase is informed by a comprehensive parametric analysis, which considers various factors affecting the performance of drones during hover (stationary flight), vertical climb (ascending flight), and forward flight. The analysis is based on the principles of simplified rotorcraft momentum theory, a foundational concept in rotorcraft engineering. These Martian drone concepts are tailored to address the more challenging mission requirements that future Martian exploration missions are likely to demand. These requirements may include extended flight durations, increased payload capacity to accommodate scientific instruments, and the ability to cover larger areas on the Martian surface. Importantly, the designs are constrained by the maximum size of the spacecraft aeroshell, ensuring that they can be safely transported to Mars within the confines of the protective aeroshell. Among the various configurations considered in this study, a tandem rotorcraft configuration emerged as the most efficient option. This configuration is expected to attain a balance between performance, endurance, and payload capacity, making it a promising choice for future Martian aerobot missions. In contrast, the analysis revealed that a conventional single main rotor configuration within the defined parameters performed poorly in meeting the requirements of the mission.
Keywords: Space vehicles; Mars; Parametric study; Helicopters; Rotors; Mathematical models; Batteries